(5x+8)(18x-53)=0

Simple and best practice solution for (5x+8)(18x-53)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+8)(18x-53)=0 equation:


Simplifying
(5x + 8)(18x + -53) = 0

Reorder the terms:
(8 + 5x)(18x + -53) = 0

Reorder the terms:
(8 + 5x)(-53 + 18x) = 0

Multiply (8 + 5x) * (-53 + 18x)
(8(-53 + 18x) + 5x * (-53 + 18x)) = 0
((-53 * 8 + 18x * 8) + 5x * (-53 + 18x)) = 0
((-424 + 144x) + 5x * (-53 + 18x)) = 0
(-424 + 144x + (-53 * 5x + 18x * 5x)) = 0
(-424 + 144x + (-265x + 90x2)) = 0

Combine like terms: 144x + -265x = -121x
(-424 + -121x + 90x2) = 0

Solving
-424 + -121x + 90x2 = 0

Solving for variable 'x'.

Factor a trinomial.
(-8 + -5x)(53 + -18x) = 0

Subproblem 1

Set the factor '(-8 + -5x)' equal to zero and attempt to solve: Simplifying -8 + -5x = 0 Solving -8 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -5x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -5x = 0 + 8 -5x = 0 + 8 Combine like terms: 0 + 8 = 8 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6

Subproblem 2

Set the factor '(53 + -18x)' equal to zero and attempt to solve: Simplifying 53 + -18x = 0 Solving 53 + -18x = 0 Move all terms containing x to the left, all other terms to the right. Add '-53' to each side of the equation. 53 + -53 + -18x = 0 + -53 Combine like terms: 53 + -53 = 0 0 + -18x = 0 + -53 -18x = 0 + -53 Combine like terms: 0 + -53 = -53 -18x = -53 Divide each side by '-18'. x = 2.944444444 Simplifying x = 2.944444444

Solution

x = {-1.6, 2.944444444}

See similar equations:

| z^4-22z^2+z=-112 | | 18=1.5k | | 2x-27+y=180 | | 2x-10x+3=0 | | 8y^3(-3y^2)= | | -12-n+n^2=0 | | A^2+9+20=0 | | 6-4x=5x+114 | | 3x=2.5(x+10) | | -24-5m+m^2=0 | | -3-(2-5p)=0 | | 18x^3+18x=0 | | 3+10=-x+14 | | 0.66x+1.5x=10 | | Y=1.75X+35500 | | 48+14a+a^2=0 | | 12x-13+45x=-2x-13-x | | 15x^2-55x=20 | | 5x-3=-14+6x | | 10-7x=-2x-45 | | -2+x+x^2=0 | | 6x+5=2x-27 | | 2x+17x-23x=12-24+36 | | (10a+3)+(9a+2)= | | 36x^2+12x=-1 | | 49-14n+n^2=0 | | 64-3g^2-2= | | 9n+n-3n=14 | | -8=w+-10 | | 135=6(4x-2)-3x | | 3+4x=-41 | | 10x+1.25=100 |

Equations solver categories